Internet 0f Things (IoT): Design and Build Micro Climate System Control in Greenhouse - Dodi Yudo Setyawan; Heri Setiawan; Qorri Indah Saputri; Bambang Fitriadi Wiansyah (Proceeding International Conference on Information Technology and Business, 2021)
Conventional greenhouse technology has been replaced by the development of Smart Farming. In green house that use smart farming technology, there is monitoring and control system. The measurable growth factors for tomatoare temperature, room humidity and soil moisture. Regional characteristics and climate factors are often unpredictable and cause these factors to inhibit the growth of tomato. In this system, it is made by monitoring and controlling roomtemperature, soil moisture according to the needs of tomato. In this system, to detect temperature and soil moisture, the DHT11 sensor is used, while the soil moisture sensor is used to detect soil moisture. NodeMCU ESP8266 acts as the mainbrain or microcontroller in the Micro Climate System. This monitoring system can measure temperature, room humidity and soil moisture levels, and can control the system to match the appropriate parameters.Keywords- Internet of Things, tomato, Smart farming, Greenhouse, Controlling, Monitoring